The Effect of eWOM Social Media on Purchase Intention: The Role Moderation of Involvement - Afandi, Mochammad Farid; Adove, Diddo Adding; Destari, Fajar (KnE Social Sciences, 2024)
The aim of this study was to examine and analyze the effect of electronic word of mouth (eWOM) on purchase intentions with high involvement as moderation. The research sample was 390 college students. Hypothesis testing used multiple regression analysis and moderation regression methods with SPSS software version 26. This research analyzed the effect of eWOM social media on components of the information adoption model (IAM) including information quality, information credibility, information usefulness and information adoption. The results showed that there was a significant effect between information quality and information credibility on purchase intention. Information usefulness and information adoption have no significant effect on purchase intention. High involvement moderates the effect of eWOM on purchase intentions. Keywords: electronic word of mouth, purchase intentions, high involvement, IAM